The analysis of achieving TCP fairness in IEEE 802.11 infrastructure WLAN - Rasul, Tareq; Othman, Mohamed (2009)
This paper raising the TCP fairness issues that reviewed from three aspects; per-flow, per-station, and per-rate based on the IEEE 802.11 Wireless Local Area Networks (WLANs) environment. Due to the strong drive towards wireless Internet access via mobile devices, these issues must be carefully handled in order to build improved systems. We succinctly review and categorize the TCP fairness characteristic and then outline the problems and solutions from previous works through comparative table. Finally, we considered the future direction for solving these problems. Overall this paper summarizes current state of knowledge of the WLAN TCP fairness.